Agenda-setting and framing in foreign policy: the case of Russian and Ukrainian televised coverage of the Crimea case - Krutikova, Yuliia (2019)
This article seeks to explore the role Russian and Ukrainian conventional media played as agenda-setters and producers of subjective framings within the context of the Crimean crisis, exploring at the same time the relationship between state and media and the impact of media representations on national public opinions. The analysis shows that agenda-setting and framing at the level of states’ policies have a fundamental role in decision-shaping and perception-building, highlighting that the manipulation of information through narrativeconstruction is a powerful tool at the service of politics. This study contributes to validate the idea that media can be perceived as key influencers of the public agenda as they emerge as the most relevant agents in mediatising politics, becoming hence a functional gatekeeper that might either facilitate the official discourse or instead obstruct it.